Peran Film dan Media Sosial Terhadap Perkembangan Budaya: Perspektif Komunikasi Pembangunan - Hanief, Lalita; Hairunnisa; Rahmawati, Yulia (JURNAL KOMUNIKATIO, 2026)
Film, as a form of mass communication, plays a strategic role in the process of social inheritance and the transmission of cultural values ​​to society. Film functions not only as a medium of entertainment but also as a means of cultural education capable of conveying and reproducing social values ​​in society. On the other hand, the development of social media has also expanded the space for cultural communication to be more open, participatory, and dialogical. Social media allows people to no longer act solely as recipients of cultural messages, but also as active producers and disseminators of cultural content, thus making the process of cultural inheritance more dynamic and sustainable. This article aims to examine the role of film as a medium for social inheritance and cultural values, as well as the role of social media in the development of development communication. This research uses a descriptive qualitative approach with data collection techniques through literature studies of relevant scientific journals and documentation of the films studied. The films analyzed include Laskar Pelangi, Ngeri-Ngeri Sedap, and Tenggelamnya Kapal Van Der Wijck as representatives of Indonesian films that promote local cultural values. The results of the study indicate that film is able to carry out the function of social and cultural inheritance through the representation of moral values, traditions, and local cultural identity. Social media plays a role in cultural development through the digital preservation and dissemination of local culture from a development communication perspective.